Effects of bioactive peptides combined with probiotics on serum uric acid in patients with hyperuricemia - HAN Dan，ZHAO Ya，HUANG Enshan，YE Shuhua，WANG Wanjin，WU Fangmin，WANG Dingliang，ZHANG Ronghua (预防医学)
Objective: To evaluate the effect of bioactive peptides combined with probiotics on serum uric acid (SUA) in patients with hyperuricemia (HUA), so as to provide the evidence for prevention and treatment of HUA. Methods: The patients with HUA aged 18 to 65 years were selected and randomly divided into an intervention group and a control group. The patients in the intervention group received bioactive peptides combined with probiotics for 28 days at a dose of 3 g/d, while the patients in the control group received an equal dose of placebos. Demographic information, body mass index (BMI), blood pressure and blood lipid were collected through questionnaire surveys, physical examination and laboratory tests. SUA levels were detected before and after 14 days and 28 days of interventions. The differences of SUA levels between the two groups were compared using generalized estimation equation. Results: Totally 108 patients with HUA were recruited, including 54 patients in the intervention group and 53 patients in the control group (1 dropout). Before interventions, there were no statistically significant differences in gender, age, course of HUA, exercise duration, frequency of alcohol consumption, frequency of meat broth consumption, BMI, prevalence of hypertension and prevalence of dyslipidemia between the two groups (all P>0.05). After 14 days of interventions, the SUA levels of the patients in the intervention group decreased by 3.00 μmol/L, while those in the control group increased by 7.00 μmol/L. After 28 days of interventions, the SUA levels of the patients in the intervention group and the control group decreased by 26.00 μmol/L and 16.00 μmol/L, respectively. However, there was no statistically significant interaction between the intervention time and group (both P>0.05). Subgroup analysis showed that after 28 days of interventions, the decrease in SUA levels in the patients aged 55 years and older and without hypertension in the intervention group was greater than those in the control group (both P<0.05). Conclusions: Bioactive peptides combined with probiotics showed no significant difference in reducing SUA levels in patients with HUA compared to the control group. The effect was more significant for patients aged 55 years and older and without hypertension.